Comparative transcriptomic analyses of Zymoseptoria tritici strains show complex lifestyle transitions and intraspecific variability in transcription profiles. (8th February 2016) - Palma‐Guerrero, Javier; Torriani, Stefano F. F.; Zala, Marcello; Carter, Dee; Courbot, Mikaël; Rudd, Jason J.; McDonald, Bruce A.; Croll, Daniel
Summary: Zymoseptoria tritici causes Septoria tritici blotch (STB) on wheat. The disease interaction is characterized by clearly defined temporal phases of infection, ultimately resulting in the death of host tissue. Zymoseptoria tritici is a highly polymorphic species with significant intraspecific variation in virulence profiles. We generated a deep transcriptomic sequencing dataset spanning the entire time course of an infection using a previously uncharacterized, highly virulent Z. tritici strain isolated from a Swiss wheat field. We found that seven clusters of gene transcription profiles explained the progression of the infection. The earliest highly up‐regulated genes included chloroperoxidases, which may help the fungus cope with plant defences. The onset of necrotrophy was characterized by a concerted up‐regulation of proteases, plant cell wall‐degrading enzymes and lipases. Functions related to nutrition and growth characterized late necrotrophy and the transition to saprotrophic growth on dead plant tissue. We found that the peak up‐regulation of genes essential for mating coincided with the necrotrophic phase. We performed an intraspecies comparative transcriptomics analysis using a comparable time course infection experiment of the genome reference isolate IPO323. Major components of the fungal infection transcriptome were conserved between the two strains. However, individual small, secreted proteins, proteases and cell wall‐degrading enzymes showed strongly differentiated transcriptional profiles between isolates. Our analyses illustrate that successful STB infections involve complex transcriptomic remodelling to up‐regulate distinct gene functions. Heterogeneity in transcriptomes among isolates may explain some of the considerable variation in virulence and host specialization found within the species.